Assessment of Dyslipidemia and Hypercholesterolemia among Patients from two Hospitals in Basra City : Penilaian Dislipidemia dan Hiperkolesterolemia pada Pasien dari Dua Rumah Sakit di Kota Basra - Saged S. Hassan; Nader A. Salman; Shahla Ali Hassan (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Cholesterol and triglycerides are essential lipids involved in cellular function and energy metabolism, yet abnormal levels are closely associated with cardiovascular disease. Specific Background: Lipid profiles are known to vary with age and gender, but local data from Basra City remain limited. Knowledge Gap: There is insufficient hospital-based evidence describing age- and gender-related patterns of dyslipidemia among patients in Basra. Aims: This study examined cholesterol and triglyceride levels in relation to age and gender among patients from two major hospitals in Basra City. Results: Data from 100 patients aged 13–79 years showed higher triglyceride levels in older adults compared to younger groups. Hypercholesterolemia was more frequent in males than females, with 20% of males and 16% of females exceeding 239 mg/dL. Borderline cholesterol levels were also more prevalent in males. Triglyceride abnormalities followed a similar trend, although gender differences were not statistically significant. Novelty: The study provides recent hospital-based lipid profile data specific to Basra City, highlighting demographic variations. Implications: These findings support the importance of age- and gender-sensitive screening strategies for dyslipidemia in clinical practice. Keywords: Triglycerides, Cholesterol, Age Differences, Gender Differences, Basra City Key Findings Highlights: Lipid abnormalities increased progressively with advancing age among patients. Male patients exhibited higher rates of elevated cholesterol levels than females. Triglyceride distributions showed demographic variation linked to lifestyle factors.